Diversidad de macrófitas acuáticas en las afluentes del río Itaya (San José, Ullpa Caño Y Moena Caño), Loreto – Perú – 2022 - Apaclla Pérez, Raúl José (2024)
This research was conducted in the water bodies of the communities of San José, Ullpa Caño, and Moena Caño, with the objective of identifying and determining the diversity of aquatic macrophytes in the tributaries of the Itaya River. Quadrant methodology and the herbarium of botanical samples at the Herbarium Amazonense (AMAZ) were used. Four biological indices were applied: Shannon, Pielou, Simpson's dominance, and Sorensen, to evaluate the richness, abundance, dominance, and similarity of the collected species. The results showed that the highest species richness was recorded in San José with a Shannon index of 1.41, while the lowest index was observed in Moena Caño with 1.18. Diversity was low in all communities, with a Pielou index of 0.10. Ullpa Caño had the highest species dominance with a Simpson index of 0.43, and San José the lowest with 0.30. The Sorensen similarity index indicated that the species in the three zones are moderately similar, with a value of 30. It is concluded that San José has medium diversity, while Ullpa Caño and Moena Caño have low diversity. The abundance and dominance of aquatic macrophytes vary significantly among the communities, highlighting the need for specific conservation strategies to maintain biodiversity in these ecosystems. An illustrated catalog of the aquatic macrophytes found was developed, providing a valuable tool for future research and environmental management in the region.